2017
DOI: 10.1002/ejhf.860
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension due to left heart disease: analysis of survival according to the haemodynamic classification of the 2015 ESC/ERS guidelines and insights for future changes

Abstract: Patients with Ipc-PH have a better prognosis compared with patients with Cpc-PH and with patients with isolated increase of PVR or DPG. Pulmonary vascular resistance has a better predictive value than DPG in patients with PH-LHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
102
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 19 publications
10
102
0
4
Order By: Relevance
“…At present, an almost equal number of studies have confirmed [41][42][43] or refuted [44][45][46] the prognostic relevance of DPG. These discrepancies are explained by the fact that the DPG represents a small number, is exposed to instability, as shown in studies where high DPGs were sometimes found in patients with a normal PVR 44 or where DPG was reported as negative in a proportion of patients, 47 conditions which are both physiologically impossible.…”
Section: The Diastolic Pulmonary Pressure Gradientmentioning
confidence: 98%
“…At present, an almost equal number of studies have confirmed [41][42][43] or refuted [44][45][46] the prognostic relevance of DPG. These discrepancies are explained by the fact that the DPG represents a small number, is exposed to instability, as shown in studies where high DPGs were sometimes found in patients with a normal PVR 44 or where DPG was reported as negative in a proportion of patients, 47 conditions which are both physiologically impossible.…”
Section: The Diastolic Pulmonary Pressure Gradientmentioning
confidence: 98%
“…First, all haemodynamic parameters measured by RHC, including PAP, are dependent on blood pressure, cardiac function (CO, LV, and RV function), and blood volume. Second, neither the TPG nor the DPG has clearly shown any incremental prognostic value (rehospitalization and cardiovascular death) . Third, PVC and PVRs seem to be the two most interesting parameters, but they are strongly related to the CO and therefore cannot be interpreted independently …”
Section: Do the Various Definitions Of Post‐capillary Pulmonary Hypermentioning
confidence: 93%
“…Consequently, the prevalence of PH in these cohorts is particularly high and cannot be extrapolated to the overall population of HF patients . Regarding the prevalence of increased DPG, it is estimated to range between 12% and 38% in HF patients . Cpc‐PH is rare in CHF and characterized by younger age, chronic obstructive pulmonary disease, and worse RV–PA coupling.…”
Section: Do the Various Definitions Of Post‐capillary Pulmonary Hypermentioning
confidence: 99%
“…The authors also showed that, in addition to PVR, pulmonary arterial compliance (PAC), calculated as stroke volume divided by pulse pressure (difference between systolic and diastolic PAP), was also predictive of survival. In fact, a low PAC turned out to be the strongest predictor of death when analysed as a continuous variable ( P = 0.001) …”
mentioning
confidence: 98%
“…In this issue of the Journal, Palazzini et al . add another piece to the puzzle . They present a retrospective, single‐centre analysis of 276 patients with LHD who underwent invasive haemodynamic assessment between 1997 and 2015, in whom post‐capillary PH (mean PAP ≥25 mmHg; mean PAWP >15 mmHg) was diagnosed.…”
mentioning
confidence: 99%